Tritium distribution in environmental compartments of the impact zone of radioactively contaminated areas - Natalya Larionova; Lyubov Timonova; Anna Toporova; Almira Aidarkhanova (Ecological Indicators)
Tritium (3H) remains a prominent radionuclide detected in notable quantities in all environmental compartments of the Semipalatinsk Test Site (STS). This study presents data describing the levels of 3H travel in areas of the impact zones of radioactively contaminated STS locations — the Degelen site. Water, soil, sediments, air, and fluorite ore (Karadzhanly deposit product) 3H activity concentrations (including the speciation) were measured using liquid scintillation with spectrometric equipment “TRI-CARB 2900 TR” (PerkinElmer, USA). Plant samples were measured using “QUANTULUS 1220” (PerkinElmer, USA). Plant samples were measured using “QUANTULUS 1220” (PerkinElmer, USA). The high values were set in free water 3H in plants (TFWT) – up to 41 kBq/kg, in soils and bottom sediments (TSAW) – 29 and 26 kBq/kg, respectively. The main source of 3H entering the environmental components is groundwater – up to 78 kBq/kg. Annual effective internal dose from 3H to personnel during operations at the Karadzhally fluorite deposit does not exceed Standards.